PENGARUH MEDIA SOSIAL MARKETING DAN CITRA MEREK TERHADAP MINTA BELI KONSUMEN PROYEK BISNIS KAKU - Novanda Crysma Terrasista; Helena Sidharta (Universitas Ciputra Surabaya, 2022)
This research is done to find out the effect of social media marketing and brand image on consumer buying interest in KAKU business project. By knowing the influence of social media marketing and brand image on consumer buying interest, it is hoped that KAKU will be able to increase the buying interest of potential consumers. If buying interest has increased, it is expected that prospective consumers can make purchases at KAKU. In this research, 4 indicators were used for buying interest, namely AIDA which stands for attention, interest, desire, and action. 5 indicators are used to measure social media marketing variables and 4 indicators are used to measure brand image. This research was conducted with reference to primary data obtained from the results of distributing questionnaires. The selected population is female followers of social media marketing Instagram KAKU business project. Sample calculation is done by using the Slovin formula. The sampling method used in this research is non-probability sampling using purposive sampling technique. Data was collected using a questionnaire via Google Form which was distributed to women followers of social media marketing Instagram KAKU business project with a total of 131 respondents. The data analysis method used in this study was Statistical Product and Service Solutions (SPSS) with multiple linear regression analysis techniques. The results in this research indicate that there is a significant influence between social media marketing and brand image on consumer buying interest in the KAKU business project. With this result, KAKU must improve its marketing through social media and maintain its brand image to remain positive in the perception of its target market.